Pengembangan Media Pembelajaran Articulate Storyline 3 Pada Pembelajaran Pendidikan Pancasila Menggunakan Model Problem Based Learning (PBL) di Kelas V SD Wilayah 1 Pauh Kota Padang - Yuliasati, Anisa; Mansurdin, Mansurdin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to develop learning media based on Articulate Storyline 3 using the Problem Based Learning (PBL) model to enhance students' understanding and motivation in the subject of Pancasila Education. This research uses a Research and Development (R&D) approach with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects include expert validators, fifth-grade teachers, and fifth-grade students from three elementary schools in area 1 Pauh. The instruments used include validation sheets, practicality questionnaires, and learning outcome tests. The generated data is analyzed quantitatively in a descriptive manner. The research results show that the developed learning media falls into the very valid category with an average percentage of 91.3%, consisting of material expert validation at 90%, language expert at 94%, and media expert at 90%. The practicality test yielded an average score of 99.33% categorized as 'Very Practical,' including the practicality for teachers at 99.33% and students at 98%. Furthermore, this media has also proven effective in improving student learning outcomes on the material 'Caring for the Unitary State of the Republic of Indonesia with Unity and Solidarity.' Based on these results, it can be concluded that this learning media is suitable to be used as an innovative alternative in Pancasila education learning in grade V of elementary school.